2011
DOI: 10.1177/0022034510385937
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Fluoride in Children Exposed to Different Sources of Systemic Fluoride

Abstract: There has been no comparison between fluoride concentrations in urine and nails of children exposed to different sources of systemic fluoride. The aim of this study was to compare the relationship between fluoride intake with urinary fluoride excretion and fluoride concentrations in fingernails and toenails of children receiving fluoride from artificially fluoridated water (0.6-0.8 mg F/L, n = 25), naturally fluoridated water (0.6-0.9 mg F/L, n = 21), fluoridated salt (180-200 mg F/Kg, n = 26), and fluoridated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
15
2
1
Order By: Relevance
“…Furthermore, once F − is incorporated into nail at growth end, it will be unaffected by more recent F − intake and physiological variables (Whitford, 2005). Fingernail analysis of F − has previously been used to assess low-level exposures in communities with fluoridation of water, tooth paste, salt, and milk use (e.g., Buzalaf et al, 2011; Lima-Arsati et al, 2010; de Almeida et al, 2007; Buzalaf et al, 2006; Pessan et al, 2005; Levy et al, 2004; Whitford et al, 1999), but epidemiological studies that evaluate the suitability and sensitivity of this biomarker in populations with endemic fluorosis are virtually absent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, once F − is incorporated into nail at growth end, it will be unaffected by more recent F − intake and physiological variables (Whitford, 2005). Fingernail analysis of F − has previously been used to assess low-level exposures in communities with fluoridation of water, tooth paste, salt, and milk use (e.g., Buzalaf et al, 2011; Lima-Arsati et al, 2010; de Almeida et al, 2007; Buzalaf et al, 2006; Pessan et al, 2005; Levy et al, 2004; Whitford et al, 1999), but epidemiological studies that evaluate the suitability and sensitivity of this biomarker in populations with endemic fluorosis are virtually absent.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers assess biological processes in response to an intervention, such as exposures to CWF, through the identification of cellular, biochemical or molecular alterations in biological media, including human tissues, cells or fluids . For fluoride exposures, several historical (bone and teeth), recent (hair and nails) and contemporary (urine, plasma, milk, sweat and saliva) biomarkers have been identified . From the perspective of conducting an epidemiological study, the most studied recent biomarkers are nails, hair and urine, all of which are collected noninvasively, making data collection more ethically and logistically feasible.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,10 Omena et al 8 evaluated fluoride intake from drinking water and from fluoride toothpaste, without considering Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…al. 9 reported fluoride intake from the entire diet (water, other beverages and solid foods) and fluoride toothpaste in a city with naturally fluoridated water. In addition, Lima et al 10 evaluated fluoride intake from diet (liquid and solid foods) and fluoride toothpaste in a city with artificially fluoridated water; however, the authors reported a low intake of water maybe because children spent most of their time in the classroom.…”
Section: Introductionmentioning
confidence: 99%